JOB OPPORTUNITIES FOR FRESH GRADUATES BASED ON INDUSTRY PARTNERSHIP MODEL IN NORTH SUMATRA PROVINCE - Muhammad Yusuf; Eko Wahyu Nugrahadi; Khairuddin Ependi Tambunan; Kornelius Harefa (CERED Indonesia Institute, 2021)
This study aims to examine the partnership model of the Industrial World to Expand Em-ployment Opportunities for Higher Education Graduates in Sumatra Province by examin-ing the variables of graduate quality, internship experience and skills on job op-portunities. This research was conducted in Medan, North Sumatra with the sample of this research being graduates of economics degree from PTN and PTS in Medan City. There were 156 respondents who graduated at the end of December 2020 in ten economic facul-ties. The results of the study based on multiple regression test showed that all variables had a significant effect on job opportunities. This proves that internship experience is im-portant for students because it affects their competitiveness to get a job after graduating from college. The limitation of this research is that the number of samples is too small so that the generalizability is very small. The recommendation of this research for the next study is to increase the number of samples and a wider research area